2019
DOI: 10.1021/acs.est.8b06574
|View full text |Cite
|
Sign up to set email alerts
|

Triplet-State Photochemistry of Dissolved Organic Matter: Triplet-State Energy Distribution and Surface Electric Charge Conditions

Abstract: Excited triplet states of chromophoric dissolved organic matter (3CDOM*) are highly reactive species in sunlit surface waters and play a critical role in reactive oxygen species (ROS) formation and pollutant attenuation. In the present study, a series of chemical probes, including sorbic acid, sorbic alcohol, sorbic amine, trimethylphenol, and furfuryl alcohol, were employed to quantitatively determine 3CDOM* and 1O2 in various organic matters. Using a high concentration of sorbic alcohol as high-energy triple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
124
3
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(153 citation statements)
references
References 55 publications
19
124
3
4
Order By: Relevance
“…This is nearly 260 times higher than the average quantum yield of q OH. Our quantum yields for singlet oxygen formation in PM extracts are similar to values previously reported for surface water organics (e.g., 2 %-5 % in Zhou et al (2019).…”
Section: Singlet Molecular Oxygensupporting
confidence: 90%
See 1 more Smart Citation
“…This is nearly 260 times higher than the average quantum yield of q OH. Our quantum yields for singlet oxygen formation in PM extracts are similar to values previously reported for surface water organics (e.g., 2 %-5 % in Zhou et al (2019).…”
Section: Singlet Molecular Oxygensupporting
confidence: 90%
“…The average (±1σ ) oxidizing triplet quantum yield in standard extracts is (2.4 ± 1.0) % (Table S13), approximately 2 times lower than the value for 1 O 2 * (Table S7) but 150 times higher than for q OH (Table S3). Our triplet quantum yields are within the wide range of values that has been reported for surface waters, approximately 0.4 %-7 % (Zepp et al, 1985;Grebel et al, 2011;Zhou et al, 2019).…”
Section: Triplet Excited States Of Organic Matter ( 3 C * )supporting
confidence: 86%
“…Lin et al (2014) showed the reaction ability and transformation mechanism of 3 CDOM* formed by humic acid using the TMP probe. Zhou et al (2019) has reported the 3 CDOM* energy distribution using TMP and SA probes. Compared with other chemical probes, TMP contains methyl-substituted groups that can be used as electron donors for 3 CDOM* reactions; thus, TMP has a higher reactivity (Canonica & Freiburghaus, 2001).…”
Section: /25mentioning
confidence: 99%
“…The energy levels of different 3 CDOM* is different. TMP, as a triplet-state probe used in this study, has remarkable electron transfer characteristics and is related to the energy of 3 CDOM* (Zhou et al, 2019). Approximately 70% of high-energy 3 CDOM* https://doi.org/10.5194/acp-2019-1032 Preprint.…”
Section: /25mentioning
confidence: 99%
See 1 more Smart Citation